2007
DOI: 10.1016/j.ejcts.2007.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of perioperative infusion of levosimendan in patients with compromised cardiac function undergoing open-heart surgery: importance of early use

Abstract: Levosimendan is a safe and efficient choice in the management of low-output syndrome during and after open-heart surgery. The shortening of hospitalisation and the trend for better outcome confirm its clear superiority when the infusion starts from the operating theatre.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 21 publications
0
42
1
1
Order By: Relevance
“…It must be highlighted, however, that ''severe LCOS'' occurred rarely in both groups with no cardiac arrest nor the need for ECMO, suggesting that a larger cohort of patients was needed to achieve a significant result. The major concern with the use of levosimendan regarded its vasodilation properties that could have resulted in excessive hypotension or increased need for vasopressors: for this reason the dose was limited to the lowest described in adults and no boluses were administered [23] while the infusion was prolonged for 72 h. Our data showed that the dual inodilator strategy (levosimendan added to milrinone) did not cause a MAP reduction or an IS increase in the study group. Instead, early lactate levels, IS, and HR were reduced in levosimendan patients.…”
Section: Discussionmentioning
confidence: 71%
“…It must be highlighted, however, that ''severe LCOS'' occurred rarely in both groups with no cardiac arrest nor the need for ECMO, suggesting that a larger cohort of patients was needed to achieve a significant result. The major concern with the use of levosimendan regarded its vasodilation properties that could have resulted in excessive hypotension or increased need for vasopressors: for this reason the dose was limited to the lowest described in adults and no boluses were administered [23] while the infusion was prolonged for 72 h. Our data showed that the dual inodilator strategy (levosimendan added to milrinone) did not cause a MAP reduction or an IS increase in the study group. Instead, early lactate levels, IS, and HR were reduced in levosimendan patients.…”
Section: Discussionmentioning
confidence: 71%
“…Our study demonstrates that prophylactic levosimendan provides positive inotropy and vasodilatation and better tissue perfusion with neutral effect on O2 consumption as manifested by significantly higher SVO2 and SCVO2 in post CPB(SVO2-78.22±4. [24] . Momeni et al found in their study that myocardial oxygen demand is significantly less in levosimendan gr.…”
Section: Discussionmentioning
confidence: 99%
“…Levosimendan before CABG showed evidence of less myocardial damage, suggestive of a preconditioning effect Tasouli et al 42 45 Determine the proper time for its infusion during or after open-heart surgery to avoid complications related with lowoutput syndrome and high dosage of inotropes Levosimendan is a safe and effi cient choice in the management of lowoutput syndrome during and after CABG CABG, coronary artery bypass grafting; CPB, cardiopulmonary bypass; IABP, intra-aortic balloon pumping gram. 31 The administration of levosimendan in patients with coronary syndrome results in an effective hemodynamic improvement.…”
Section: Use Of Levosimendan In Patients Undergoing Percutaneous Coromentioning
confidence: 99%